Meningkatkan Kematangan Karier Peserta Didik SMA dengan Pelatihan Reach Your Dreams dan Konseling Karier - Ahmad Saifuddin; Lisnawati Ruhaena; Wiwien Dinar Pratisti (Faculty of Psychology, Universitas Gadjah Mada, 2017)
Career maturity is a condition that needed to choice the program in higher level study. Henceforth, the low level of career maturity in senior high school student has to be solved with the comprehensive intervention as soon as possible. The purpose of this research is to know the effectivity of Reach Your Dreams Training and career counseling for improving career maturity in senior high school student. This research used Solomon Six Group Design. Subjects of this research are 42 senior high school students with average level of career maturity who are divided into two groups given Reach Your Dreams Training, two groups given career counseling, and two control groups. According to the result, the conclusion of this research is Reach Your Dreams Training and Counseling Career can improve career maturity level in senior high school students effectively. It is caused by the effect of Reach Your Dreams Training and career counseling, and not caused by the effect of pretest.